The Study the Effect of Type and Duration of Treatment on Some Hematological and Biochemical Variables of Lymphoma Patients in Al-Muthanna Province, Iraq - Sarah Sakban Hasan; .Hanaa Ali Aziz (Tikrit Journal of Pure Science, 2024)
The term "malignant lymphoma" describes primary cancers of the lymphoreticular system, almost all of which begin as lymphocytes. This study aimed to assess the impact of therapy type and duration on several hematological and biochemical parameters in lymphoma patients. The study was conducted from July 2023 to October 2023. This study examined one hundred samples in total, fifty sample as control group and fifty sample as patients group. The age range of the participants was between 5 and 77 years old. Some hematological and biochemical tests were analyzed in the current study. The study showed a significant  increase (P<0.05) according to type and duration of therapy in patient groups. The study indicated a significant  decrease (P<0.05) in red blood cells(RBC), hemoglobin (Hb), lymphocyte and  basophils  compared  with  control   groups, but indicated a significant increase (P<0.05) in white blood cells (WBC), neutrophils and platelets compared with control groups. Also, the study showed a significant increase (P<0.05) in urea, creatinine, alanine aminotransferase(ALT) and aspartate transaminase (AST) compared with control   groups.